124k views
23 votes
Help me pleaseeeeeeeeeeeeeeeeeeeeeeeeeeeee

Help me pleaseeeeeeeeeeeeeeeeeeeeeeeeeeeee-example-1

1 Answer

10 votes

Since the variable x is the numerator of the fraction, we first need to multiply each side by 6, since the denominator is 6. After doing this, the equation should now look like this:
18 = x + 31. Next, we subtract 31 from 18 following the rule. 18 - 31 = -13. x is equal to -13.

For shown work in order:


(6) 3 = x +31


18 = x + 31


18 - 31 = x


x = -13

User Thebjorn
by
4.1k points